2004
DOI: 10.1152/physiolgenomics.00138.2004
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the osteopontin promoter affect its transcriptional activity

Abstract: .-Understanding the molecular mechanisms that underlie regulation of transcription of the human osteopontin encoding gene (OPN) may help to clarify several processes, such as fibrotic evolution of organ damage, tumorigenesis and metastasis, and immune response, in which OPN overexpression is observed. With the aim to evaluate variants with functional effect on transcription, we have analyzed the promoter region and focused our investigation on three common variants present in the first 500 bp upstream of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
136
1
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(147 citation statements)
references
References 47 publications
7
136
1
3
Order By: Relevance
“…Of course, the matters of expression differences and potential promoter polymorphisms of OPN are much more complicated. Giacopelli, et al [33] suggested that polymorphisms in the osteopontin promoter affect its transcriptional activity in human, and another group reported that the expression of OPN might be controlled by not only its promoter polymorphism but also by trans-activators [34]. Moreover, a report suggested that allelic polymorphism of Opn qualitatively affects on b-glucaninduced granuloma formation, and allele b OPN defected in induction of cell migration [35].…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the matters of expression differences and potential promoter polymorphisms of OPN are much more complicated. Giacopelli, et al [33] suggested that polymorphisms in the osteopontin promoter affect its transcriptional activity in human, and another group reported that the expression of OPN might be controlled by not only its promoter polymorphism but also by trans-activators [34]. Moreover, a report suggested that allelic polymorphism of Opn qualitatively affects on b-glucaninduced granuloma formation, and allele b OPN defected in induction of cell migration [35].…”
Section: Discussionmentioning
confidence: 99%
“…The G base insertion at À156 site of OPN promoter generates another Runx2-binding site, 19,22 and Runx2 bindings are crucial for regulation of OPN transcription in bone tissue. 36 As discussed above, enhanced expression of OPN in heart potentially causes cardiac dysfunction.…”
Section: Renin-angiotensin System and Opn Expressionmentioning
confidence: 99%
“…17,18 Recently, three functional polymorphisms (À66T/G, À156del/G and À443T/C) on the promoter region of OPN gene have been found to affect gene expression by altering transcriptional activity 19 and reported to be associated with several diseases, including pseudoxanthoma elasticum, stroke and chronic hepatitis C. [20][21][22] The insertion of guanine base at position À156 (À156G allele) on the OPN promoter generates a Runx2 binding site so that the binding of Runx2 factor to the À156G position promotes OPN transcription. 19 In the present study, we investigated the association between diastolic dysfunction and the À156del/G polymorphism on the OPN promoter in patients with hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Several caveats make this a difficult task: candidate SNPs might show similar association with expression differences in several nearby genes, making the pre-selection of candidate susceptibility genes difficult. In addition, a variation in a (nearby) 10 characterized three polymorphic variants of the OPN promoter, and showed that the haplotype determined the promoter activity and different alleles led to changes in the transcription factor binding affinity. Predicted transcription factor binding sites were obtained through in silico methods and confirmed using Electrophoretic Mobility Shift Assays (EMSA).…”
Section: Identifying Mechanistic Role Of Variationsmentioning
confidence: 99%